The effect of marketing mix on guest satisfaction and guest retention in five star hotels - Raeesi, Ronak (2013)
Providing customer satisfaction and retention is one of the biggest challenges in service industries. Organizations today are putting on efforts to identify and manage existing customers. Among the popular marketing theories, the 8Ps of Lovelock service marketing mix recognized the critical factor in business for competitive differentiation, customer satisfaction and customer retention. This study examines the relationship between the marketing mix components, guest satisfaction and retention. Also it investigates the mediating effect of satisfaction on the relationship between marketing mix and guests’ retention in five – star hotels in Kuala Lumpur. Furthermore, this research tries to discover the existence of difference in the level of satisfaction and retention based on nationality that the guests are Malaysian or international. In this research the non- probability and convenient sampling is chosen and by using Likert Scale’s questionnaire the data were collected from 25 five-star hotels in Kuala Lumpur. And data were analyzed according to the collected questionnaires by structural equation modeling using the Partial Least Squares (PLS) approach. During the analysis several methods were used such as, reliability and validity analysis, t-test and independent t-test. The results of this study show all the 8 Ps of marketing mix components has a positive relationship with the satisfaction and, among the marketing mix components, service or product has the largest effect on satisfaction. Furthermore nationality has not made a difference in terms of level of satisfaction and retention. This study provides hotel professionals with an assessment of Lovelock marketing mix theory to measure and manage guest satisfaction and retention in five star hotels in Kuala Lumpur.